An experimental and numerical study of the strengthening of masonry brick vaults. (January 2023) - Tanriverdi, Sukran
Abstract: Vaults are curvilinear cover systems that cover open spaces formed by the combination of arches. The vaults, built using materials such as stone and brick, are used in historical buildings such as mosques, madrasahs, inns, baths, churches, and monasteries. In this study, experimental studies were carried out to examine the reinforcement techniques with steel and different types of CFRP strip applications applied to masonry vaults. Within the scope of the research, one reference sample, one tie rod, four reinforced CFRP materials of different designs, and a total of six masonry vault samples were tested under axial compression. The test vault samples were also analyzed numerically in the LUSAS Analysis Program, and the test results obtained from the numerical analysis were compared. According to the results obtained, the load-bearing capacity of the reinforced samples increased by at least 45% compared to the non-reinforced sample that was named as the reference.